A comparison of massive MIMO using pre and post-processing - Silva, Mário Marques da (2017)
This paper considers the use of massive multiple input, multiple output (MIMO) combined with single-carrier with frequency-domain equalization (SC-FDE) modulations, associated to millimeter wave (mm-Wave) communications. A comparison of the proposed massive MIMO using pre-processing (precoding) and post-processing is performed in this paper. We consider three different types of algorithms: Zero Forcing Transmitter (ZFT), Maximum Ratio Transmitter (MRT), and Equal Gain Transmitter (EGT), both with iterative detection schemes. The advantage of both MRT and EGT relies on avoiding the computation of pseudo-inverse of matrices. The performances of MRT and EGT are very close to the matched filter bound just after a few iterations of a new proposed interference cancellation, even when the number of receive antennas is not very high.